2017
DOI: 10.1007/978-3-319-65813-1_18
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Being Average: A Mediocrity Approach to Style Masking and Author Obfuscation

Abstract: Users posting online expect to remain anonymous unless they have logged in, which is often needed for them to be able to discuss freely on various topics. Preserving the anonymity of a text's writer can be also important in some other contexts, e.g., in the case of witness protection or anonymity programs. However, each person has his/her own style of writing, which can be analyzed using stylometry, and as a result, the true identity of the author of a piece of text can be revealed even if s/he has tried to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 12 publications
0
41
0
1
Order By: Relevance
“…McDonald et al [29] Manual incorporation of suggested changes * Karadzhov et al [26] Target specific features Mansoorizadeh et al [28] Replacement with synonyms Keswani et al [27] Round trip translation Shetty et al [43] Generative Adverserial Networks (GANs)…”
Section: Obfuscation Methods Automated Evasion Semantic No Training Ementioning
confidence: 99%
See 2 more Smart Citations
“…McDonald et al [29] Manual incorporation of suggested changes * Karadzhov et al [26] Target specific features Mansoorizadeh et al [28] Replacement with synonyms Keswani et al [27] Round trip translation Shetty et al [43] Generative Adverserial Networks (GANs)…”
Section: Obfuscation Methods Automated Evasion Semantic No Training Ementioning
confidence: 99%
“…More specifically, they replaced a word with one of its synonyms obtained from WordNet [33]. Karadzhov et al [26], from PAN 2016, transformed stylometric features to their average values using different rules such as sentence splitting, stop words removal, and spelling correction to obfuscate text. The authors reported that splitting sentences and removal of certain words helps with obfuscation but significantly hurts the sensibility of the obfuscated text to a human reviewer.…”
Section: Authorship Obfuscationmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was used in Anonymouth [35], a semi-automated tool that provides feedback to authors on which features to modify to effectively anonymise their texts. A similar approach was also followed by Karadhov et al [23] as part of the PAN@Clef 2017 task.…”
Section: Related Workmentioning
confidence: 98%
“…Authorship attribution Previous work on authorship attribution and related problems (e.g., author obfuscation [3,4,12,15]) used primarily term frequencies [5,9] and features from stylometry [8,9,18]. We borrowed ideas for traditional features from [2,13], but we also designed some new ones, related to tautology, grammar contractions, quote use discrepancies, beginning and ending author statement words, and named entity spellings (see Section 3.4).…”
Section: Related Workmentioning
confidence: 99%